Hotel Heterotopia: The Locus of Crisis in El hombre solo and Esos cielos by Bernardo Atxaga - Posey, Alison (Revista Canadiense de Estudios Hispánicos, 2022)
In this article, I expand upon Olaziregi’s foundational investigation of heterotopias in El hombre solo (1994) in order to further elaborate on the function of the hotel site in both this and Atxaga’s subsequent 1995 novel, Esos cielos. Through a comparative analysis of these novels – both foundational texts in the development of new narrative of the Basque conflict in the nineteen-nineties – I argue that the hotel functions as a heterotopia of crisis, and that the protagonists’ presence there catalyzes the fundamental dilemma of contemporary Basque identity lying at the heart of both novels.